2018
DOI: 10.1038/s41586-018-0439-x
|View full text |Cite|
|
Sign up to set email alerts
|

A multi-cohort study of the immune factors associated with M. tuberculosis infection outcomes

Abstract: Most infections with Mycobacterium tuberculosis (Mtb) manifest as a clinically asymptomatic, contained state, known as latent tuberculosis infection, that affects approximately one-quarter of the global population. Although fewer than one in ten individuals eventually progress to active disease, tuberculosis is a leading cause of death from infectious disease worldwide. Despite intense efforts, immune factors that influence the infection outcomes remain poorly defined. Here we used integrated analyses of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(224 citation statements)
references
References 46 publications
16
193
1
Order By: Relevance
“…Likewise, no other cell types estimated by the 'immunoStates' signature matrix showed significant differences over time in these cohorts (P > 0.05, linear mixed model, data not shown). This result with CD4+ α/β T cells and NK cells is consistent with the conclusion that the RNA signature of time since TB exposure is independent from the RNA signature of prospective TB risk, since both T cells and NK cells are known to decrease in circulation in active TB disease (25,41).…”
Section: Time Since Tb Exposure In Humans Is Associated With Alteratisupporting
confidence: 84%
See 3 more Smart Citations
“…Likewise, no other cell types estimated by the 'immunoStates' signature matrix showed significant differences over time in these cohorts (P > 0.05, linear mixed model, data not shown). This result with CD4+ α/β T cells and NK cells is consistent with the conclusion that the RNA signature of time since TB exposure is independent from the RNA signature of prospective TB risk, since both T cells and NK cells are known to decrease in circulation in active TB disease (25,41).…”
Section: Time Since Tb Exposure In Humans Is Associated With Alteratisupporting
confidence: 84%
“…Building on this prior work, we assess RNA expression as a potential biomarker of recent exposure or infection with M.tb. Using our murine data and recently published studies in cynomolgus macaques and humans (21,22,24,25), we show for the first time that RNA expression predicts recent infection/exposure in all three species. Moreover, in both macaques and humans, these RNA signatures of recent infection/exposure are independent of the recently identified signatures of individual prospective TB disease risk.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…1c). A recent report demonstrated that TB-exposed individuals who did not progress to active disease had increased abundance of cytotoxic NK cells 20 . Only household contacts that remained asymptomatic and did not progress to active TB disease for 12 months were included in this analysis and similar to the recent report, household contacts in this cohort that did not progress had increased IFN-γ, T-bet and perforin production from NK cells compared to individuals with TB ( Fig 1b; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%